Reverse Erythroblastosis Virus α Antagonism Promotes Homocysteine Catabolism and Ammonia Clearance. Issue 5 (30th May 2019) - Zhang, Tianpeng; Chen, Min; Guo, Lianxia; Yu, Fangjun; Zhou, Cui; Xu, Haiman; Wu, Baojian
Abstract : Metabolic homeostasis of amino acids is essential for human health. Here, we aimed to investigate a potential role for the clock component reverse erythroblastosis virus α (Rev‐erbα) in circadian regulation of amino acid metabolism. RNA‐seq with Rev‐erbα ‐/‐ mice showed expression changes in genes involved in amino acid metabolism, particularly, the urea cycle and methionine metabolism. Rev‐erbα ablation increased hepatic mRNA, protein, and enzymatic activity of betaine homocysteine methyltransferase (Bhmt), cystathionine β‐synthase (Cbs), and cystathionine γ‐lyase (Cth) and decreased the levels of plasma and liver homocysteine in mice. Cell‐based assays confirmed negative regulation of these three genes by Rev‐erbα. Combined luciferase reporter, mobility‐shift, and chromatin immunoprecipitation assays identified Rev‐erbα as a transcriptional repressor of Bhmt, Cbs, and Cth . Rev‐erbα ablation or antagonism alleviated chemical‐induced hyperhomocysteinemia in mice. This was accompanied by elevated expressions of Bhmt, Cbs, and Cth. Moreover, Rev‐erbα ablation or antagonism promoted urea production and ammonia clearance. Of urea cycle–related genes, arginase 1 (Arg1), ornithine transcarbamylase (Otc), and carbamoyl‐phosphate synthase 1 (Cps1) expressions were up‐regulated in Rev‐erbα ‐/‐ mice. Negative regulation of these urea cycle genes by Rev‐erbα was validated using cell‐based experiments. Mechanistic studies revealed that Rev‐erbα inhibited CCAAT‐enhancer‐binding protein α transactivation to repress the transcription of Arg1, Cps1, and Otc . Conclusion: Rev‐erbα antagonism alleviates hyperhomocysteinemia and promotes ammonia clearance. Targeting Rev‐erbα represents an approach for the management of homocysteine‐ and ammonia‐related diseases.